The Doctor's Dilemma - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Doctor's Dilemma" by Bernard Shaw is a play first staged in 1906. It explores moral conflicts created by limited medical resources when a doctor discovers a tuberculosis cure but can only treat ten patients. When asked to save one more person, he must choose between a selfless medical colleague or a brilliant but immoral artist$1 (Ba decision complicated by his attraction to the artist's wife. The play satirizes the medical profession's tension between public service and private gain. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Doctor%27s_Dilemma_(play)
Release date is 2004-02-01
Eve Sobol and David Widger
Keywords: Physicians -- Drama